PENETAPAN PARAMETER NON SPESIFIK DAN SPESIFIK EKSTRAK DAUN SALAM (Syzgium polyanthum) - Lina Widiyastuti; Widyasari Putranti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Bay leaf extract is one of the traditional medicinal ingredients which is efficacious as an antihyperlipid. The quality of the extract is a parameter to guarantee the optimal therapeutic effect. Determination of non-specific and specific parameters of bay leaf extract (EDS) is needed to ensure the quality of raw materials used in hyperlipid therapy. The bay leaf extract was obtained from Bantul, Yogyakarta and macerated using 70% ethanol. EDS tested the parameters of ash content, water content, soluble ethanol extract content, water soluble extract content, acid insoluble ash content, quantitative qualitative analysis, total plate number analysis, analysis of yeast mold number, specific gravity, qualitative analysis. This study was obtained by EDS meeting the standardization of non-specific and specific parameters according to Indonesian Herbal Pharmacopoeia.